Soil Conservation in Ethiopia - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
CFSCDD (Community Forests and Soil Conservation Development Department) 1986, 100pp, in the series 'Guidelines for Development Agents'. The objective of this book is to simplify conservation planning while at the same time providing a sound...